Novel Reading and Insanity': Nineteenth-Century Quaker Fiction Reading Practices - Hood, James W. (Quaker studies, 2018)
Standard histories of nineteenth-century Quakerism note that fiction reading was prohibited or strongly discouraged in the Religious Society of Friends, and multiple public documents from the period indicate that pronouncements against reading fiction, especially for young people, were ubiquitous until almost the end of the century. However, records found in minutes kept by Quaker-only reading groups or in the library holdings of Quaker reading societies show that, in private or semi-private settings, Quakers were regularly acquiring fiction as early as the 1820s. Through an examination of some of these records and the histories of some Quaker reading groups, this article complicates our historical understanding of how the Religious Society of Friends adapted to a new information technology, engaging a powerful tension between their testimony of integrity and their belief in continuing revelation.